2019
DOI: 10.1097/cm9.0000000000000358
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal micro factors associated with endothelial cells

Abstract: Objective: Recent studies have shown the important influence of various micro factors on the general biological activity and function of endothelial cells (ECs). Vascular endothelial growth factor ( VEGF ) and angiogenin ( ANG ) are classic micro factors that promote proliferation, differentiation, and migration of ECs. The underlying pathophysiological mechanisms and related pathways of these micro factors remain the focus of current research.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 79 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…45,46 In addition, ANG and VEGF are two main molecular factors associated with endothelial cell functions. 47 ANG is necessary for angiogenesis, 48 and the coordinated expression of VEGF and HIF-1α is necessary for neovascularization. 49 In our study, HIF-1α, VEGF, and ANG values were correlated with each other in both recipient and donor sites, consistent with reported in vitro coordinated responses for these molecules, obtained with periodontal ligament fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45,46 In addition, ANG and VEGF are two main molecular factors associated with endothelial cell functions. 47 ANG is necessary for angiogenesis, 48 and the coordinated expression of VEGF and HIF-1α is necessary for neovascularization. 49 In our study, HIF-1α, VEGF, and ANG values were correlated with each other in both recipient and donor sites, consistent with reported in vitro coordinated responses for these molecules, obtained with periodontal ligament fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…HIF‐1α, which plays a critical role in response to hypoxic conditions, to which the harvested gingival graft tissues are exposed until revascularization is established, has been shown to stimulate ANG and VEGF production in periodontal fibroblasts 45,46 . In addition, ANG and VEGF are two main molecular factors associated with endothelial cell functions 47 . ANG is necessary for angiogenesis, 48 and the coordinated expression of VEGF and HIF‐1α is necessary for neovascularization 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Two of the Notch signaling pathway components DLL4, a transmembrane ligand for the Notch, and ephrin-B2, a downstream of DLL4/Notch, have recently appeared essential in arterial differentiation of endothelial cells (ECs). Ephrin-B2 and DLL4 could be delivered into endothelial progenitor cells (EPCs) through exosomes to promote tumor angiogenesis [ 54 , 55 ]. Kongkavitoon et al showed a link between HBx and DLL4-Notch1 in regulating cell survival in HCC.…”
Section: The Role Of Exosomes In Human Oncogenic Viruses-associated C...mentioning
confidence: 99%
“…VEGF is an autocrine basic protein, which is mainly secreted by macrophages, RPE cells, vascular endothelial cells and pericytes etc. [73,74]. Hypoxia, oncogenes and in ammatory factors are involved in the regulation of VEGF biological activity [75].…”
Section: Choroidal Neovascularizationmentioning
confidence: 99%